Mass transfer of ammonia escape and CO2 absorption in CO2 capture using ammonia solution in bubbling reactor. (15th January 2016) - Ma, Shuangchen; Chen, Gongda; Zhu, Sijie; Han, Tingting; Yu, Weijing
Graphical abstract: Highlights: Mass transfer coefficient models of ammonia escape were built. Influences of temperature, inlet CO2 and ammonia concentration were studied. Mass transfer coefficients of ammonia escape and CO2 absorption were obtained. Studies can provide the basic data as a reference guideline for process application. Abstract: The mass transfer of CO2 capture using ammonia solution in the bubbling reactor was studied; according to double film theory, the mass transfer coefficient models and interface area model were built. Through our experiments, the overall volumetric mass transfer coefficients were obtained, while the interface areas in unit volume were estimated. The volumetric mass transfer coefficients of ammonia escaping during the experiment were 1.39 × 10 −5 –4.34 × 10 −5  mol/(m 3  s Pa), and the volumetric mass transfer coefficients of CO2 absorption were 2.86 × 10 −5 –17.9 × 10 −5  mol/(m 3  s Pa). The estimated interface area of unit volume in the bubbling reactor ranged from 75.19 to 256.41 m 2 /m 3, making the bubbling reactor a viable choice to obtain higher mass transfer performance than the packed tower or spraying tower.